A novel germline (c.314T>A) SDHB variant in metastatic paraganglioma: case report and literature review - Bernardi, Stella; Zovato, Stefania; Pennelli, Gianmaria; Cavallaro, Marco; Rovina, Matteo; Dobrinja, Chiara; Guglielmi, Alessandra; Zanconati, Fabrizio; Mazzà, Daniela; Nieri, Alberto; Bartolomei, Mirco; Schiavi, Francesca (Frontiers in Endocrinology, 2025)
Introductionmost sympathetic paragangliomas are driven by germline pathogenic variants. Identifying germline succinate dehydrogenase B (SDHB) pathogenic variant has important management implications. Here we report a novel germline variant in the SDHB gene in a patient with metastatic paraganglioma and his response to available treatments.Case presentationa 37-year-old Serbian man was admitted to hospital due to hypertension, tachycardia and hyperhidrosis. Screening for secondary hypertension revealed elevated 24-h urinary normetanephrine. A CT scan showed the presence of a 54 x 76 mm retroperitoneal mass that surrounded the aorta, which was located below the pancreas and behind the duodenum. The patient was diagnosed having extra-adrenal sympathetic metastatic paraganglioma (PGL), for which we scheduled debulking surgery and genetic testing. Tumor debulking improved patient symptoms as well as signs of catecholamine excess and tumor mass effects. Meanwhile waiting for next-generation sequencing (NGS) results, the patient started a treatment with sunitinib. At this point, NGS results showed a novel and previously not reported germline SDHB c.314T>A gene variant, which was initially classified as a class 3 variant of uncertain significance. Immunohistochemistry for SDHA and SDHB showed absence of SDHB expression and allowed us to reclassify this variant as a class 4 “likely pathogenic” variant. At this stage, due to disease progression and genetic results, sunitinib was stopped and the patient started peptide receptor radionuclide therapy, which was not able to stop disease progression. In the end, the patient was treated with Averbuch chemotherapy (which is still ongoing), with an amelioration of clinical laboratory and imaging parameters.ConclusionClinical characteristics as well as data from SDHB immunohistochemistry well support reclassification of the novel germline SDHB c.314T>A gene variant as a class 4 “likely pathogenic” variant in the patient with metastatic PGL. This information might help clinicians in the management of its carriers and their families. In this case, only debulking surgery and chemotherapy with Averbuch scheme were clinically effective. Further studies are needed to better clarify and outline at which time point during the disease course SDHB patients should start Averbuch-scheme chemotherapy.